(untitled) (Research, Society and Development, 2020)
Introduction: Facial paralysis is characterized by the inability to move facial muscles, which are responsible for facial mimicry, this is due to an injury caused to the facial nerve (VII) by the cranial nerve. With regard to the causes of facial asymmetries, they can be multifactorial, being of congenital origin, acquired (due to injuries or diseases) and of development. The use of botulinum toxin has been a great ally since it offers benefits for aesthetic treatments performed by specialized professionals. Objective: Thus, the objective of this study is to report a clinical case on the application of botulinum toxin to correct facial asymmetry due to post stroke stroke. Methodology: This is a descriptive study of a clinical case report type carried out in a dental office in the city of Maceió-AL. Case report: Patient NLFS, teacher, female, 45 years old, came to the office on 01/21/2020 to make an assessment, the patient reported the following main complaint: facial asymmetry due to hemifacial paralysis on the left side of the face. Conclusion: However, it can be obtained that the treatment with Botulinum Toxin-A was effective to restore aesthetics, symmetry, function and muscle balance to the patient’s face.